ANALISIS FAKTOR KETERLAMBATAN PROYEK PEMBANGUNAN INTEGRATED LABORATORY FOR SCIENCE POLICY AND PUBLIC COMMUNICATION UNIVERSITAS JEMBER: Studi Kasus : Pembangunan Integrated Laboratory For Science Policy And Public Communication Universitas Jember - Rachmawati, Ayu; Iskandar, Tiong; Kartika, Deviany (STUDENT JOURNAL GELAGAR, 2021)
In every project development, problems often occur that hinder the completion process. A delay event on a project can be caused by one or more causes of delay (delay agent) and vice versa. The factors causing the delay are in the form of internal and external factors. This study aims to analyze the factors that cause delays in the development project of the Integrated Laboratory for Science Policy and Public Communication at the University of Jember and mitigation actions that can minimize or prevent delay events from recurring. The method used in this research is the House of Risk method which functions to analyze the causes of risk and then use the steps to analyze the causes of delay to become a House of Delay. The first stage is identification of the problem, then determining the scale of the impact of severity and probability of delay. After obtaining the rating scale, it is analyzed by the House of Risk method phase 1 to calculate the ADP (Aggregate Delay Potential) value and obtain a rating of the problem (the cause of the delay). Determined 3 problems that need to prioritize handling / mitigation action priority with the House of Risk method phase 2. After being identified based on the results of the interview there are six delay events and thirteen delay agents on the project. From the analysis results, it was found that there were three causes of delays, namely, the length of time for the delivery of materials sent from local and imported suppliers, a collision sequence on the job, and work repairs. Of the three problems, then analyzed for efforts to deal with HOR stage 2, namely comprehensive / complete material stock planning, more supervision of scheduling, and controlling techniques.